BKK INVENTORY SYSTEM FOR BAHAGIAN KOMUNIKASI KORPORAT, JABATAN PERKHIDMATAN KOMPUTER NEGERI USING PROGRESSIVE WEB - AZHAR, CHONG (Universiti Malaysia Sarawak (UNIMAS), 2023)
Bahagian Komunikasi Korporat of Jabatan Perkhidmatan Komputer Negeri is still using a manual system to record corporate gift records in their storeroom. This current manual system has some drawbacks for the productivity of the staff in this division. One of the major issues encountered by the staff is data loss and the complicated task of handling the door gift inventory records. Hence, this proposed system is aimed at developing a progressive web app (PWA) named BKK Inventory System for managing the inventory system for Bahagian Komunikasi Korporat of Jabatan Perkhidmatan Komputer Negeri. It is an inventory system that can be accessed by staff and members of Bahagian Komunikasi Korporat of Jabatan Perkhidmatan Komputer Negeri. This system will be available for both web and mobile user interfaces. This system is used to store inventory information of the corporate gift stock, maintain stock levels, update inventory, and provide inventory reports on a daily or weekly basis. Customization is what makes this system more distinctive. Users are allowed to select the best functionality for their organisation based on their needs. Users may add, remove, search for, and update data in the inventory system using this system. In addition, it enables users to create reports using the inventory system. The user can also apply for the door gift through the BKK Inventory System.